Efforts to Improve Self-Service Activities With Play Methods in The Perspective of Parenting of Parents Children with Autism - Laila Nur Rohmah; Luthfie Lufthansa; Nurcholis Istiawan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
There are still many parents who have autistic children who experience parenting problems, especially in self-help activities. Where the educational background and occupation of parents greatly influence how parenting is implemented for their daughters. One way to solutions with this problem is to provide self-development activities accompanied by movement activities with play. With the aim of ensuring that autistic children have a better and optimal quality of life, so that they can carry out self-development activities independently without expecting help from others. This research refers to a qualitative descriptive methodology. Then the data collection uses interviews, observation and documentation of parenting of autistic children. The research subjects were three parenting of autistic children in the Malang City area. The results of the research obtained are that parenting have sincerely accepted whatever their child's condition is. Movement activities carried out by parents in an effort to increase the self-development activities of autistic children are by providing outdoor activities such as walking outside the house, running, rolling, crawling, walking on footbridges, throwing and catching, bouncing a ball, cycling, swimming, zig-zag walking, brain exercises and so on. Understanding the factors that determine when dealing with autistic children requires understanding and cooperation from both parents themselves. So, good parenting and the right environment will be able to support autistic children to have optimal independence.